2012
DOI: 10.1159/000337975
|View full text |Cite
|
Sign up to set email alerts
|

When Do Short Children Realize They Are Short? Prepubertal Short Children’s Perception of Height during 24 Months of Catch-Up Growth Hormone Treatment

Abstract: Aim: To examine perceived height during the first 24 months of growth hormone (GH) treatment in short prepubertal children. Methods: Ninety-nine 3- to 11-year-old short prepubertal children with either isolated GH deficiency (n = 32) or idiopathic short stature (n = 67) participated in a 24-month randomized trial of individualized or fixed-dose GH treatment. Children’s and parents’ responses to three perceived height measures: relative height (Silhouette Apperception Test), sense of height (VAS short/tall), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…This change can be explained by the fact that children's understanding of intentionality develops at approximately 8 or 9 years of age17,18) and an increased focus on body image begins to emerge at this age19). Thus, it was further reported that at the age of approximately 8-9 years, the child begins to become aware of personal height in relation to others, at which point, short stature begins to have a negative effect upon the child's quality of life20). In this light, the lower self-concept score related to Physical Appearance and Attributes of the post-8 group can be interpreted as an age-dependent natural phenomenon arising from the change of conception.…”
Section: Discussionmentioning
confidence: 99%
“…This change can be explained by the fact that children's understanding of intentionality develops at approximately 8 or 9 years of age17,18) and an increased focus on body image begins to emerge at this age19). Thus, it was further reported that at the age of approximately 8-9 years, the child begins to become aware of personal height in relation to others, at which point, short stature begins to have a negative effect upon the child's quality of life20). In this light, the lower self-concept score related to Physical Appearance and Attributes of the post-8 group can be interpreted as an age-dependent natural phenomenon arising from the change of conception.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only because of barriers in everyday life caused by height-related physical limitations, but also because short stature can be regarded as a social stigma, which in turn may affect self-perception and the social integration of persons with short stature. The intensity of impairment depends not only on the degree of short stature, but also on the way the individuals perceive their height and their ability to cope with the stigma [19-22]. …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that taller children perceive themselves as being heavier, independent of their actual weight status. Both men and women tend to overestimate their height (38,39) and so do short children and their parents (40) . Yet very few studies have addressed the role of height on body image concerns.…”
Section: Discussionmentioning
confidence: 99%